The emerging importance of skull-brain interactions in traumatic brain injury - Goodman, Grant W.; Devlin, Patrick; West, Bryce E.; Ritzel, Rodney M. (Frontiers in Immunology, 2024)
The recent identification of skull bone marrow as a reactive hematopoietic niche that can contribute to and direct leukocyte trafficking into the meninges and brain has transformed our view of this bone structure from a solid, protective casing to a living, dynamic tissue poised to modulate brain homeostasis and neuroinflammation. This emerging concept may be highly relevant to injuries that directly impact the skull such as in traumatic brain injury (TBI). From mild concussion to severe contusion with skull fracturing, the bone marrow response of this local myeloid cell reservoir has the potential to impact not just the acute inflammatory response in the brain, but also the remodeling of the calvarium itself, influencing its response to future head impacts. If we borrow understanding from recent discoveries in other CNS immunological niches and extend them to this nascent, but growing, subfield of neuroimmunology, it is not unreasonable to consider the hematopoietic compartment in the skull may similarly play an important role in health, aging, and neurodegenerative disease following TBI. This literature review briefly summarizes the traditional role of the skull in TBI and offers some additional insights into skull-brain interactions and their potential role in affecting secondary neuroinflammation and injury outcomes.